Developing interest to share and craft based on the Technology Acceptance Model - Lee, Chien Sing *; Low, Samuel Hong Shan * (2017)
The Malaysian Ministry of Education aims to increase interest in learning Science, Technology, Engineering and Mathematics, through Science2Action. Among these initiatives in Science2Action, is the use of Art(s). By combining the Internet, technology and crafts, e-crafting is formed. This e-crafting project aims to increase awareness about what interests the audience through sharing of and development of craft, hopefully towards possibilities of ideation and mixing crafts, extending from the original craft such as origami. Designed based on the Technology Acceptance Model, findings are positive.